Understanding efficacy-safety balance of biologics in moderate-to-severe pediatric psoriasis - Golhen, Klervi; Winskill, Carolyn; Theiler, Martin; Buettcher, Michael; Yeh, Yu-Hsin; Zhang, Nancy; Welzel, Tatjana; Pfister, Marc (Frontiers in Medicine, 2022)
Background Psoriasis is a chronic immune-mediated inflammatory skin disease affecting both adults and children. To better understand the efficacy-safety profile of biologics in children with moderate-to-severe psoriasis, this study aimed to analyze efficacy and safety data of randomized controlled trials (RCTs) performed in pediatric psoriasis and to compare efficacy outcomes in children with those in adults. Methods RCTs investigating biologics in children with moderate-to-severe psoriasis were identified in a systematic literature review. PASI75/90 treatment responses at weeks 11/12 were analyzed comparing biologics with control arms. Serious adverse events (SAEs) were analyzed at the end of each study. Efficacy data from RCTs in adults with psoriasis were selected for the same biologics. Risk ratios (RR) of selected RCTs were pooled together in a statistical random effects model using the inverse variance method. Results For children, there were 1 etanercept, 2 secukinumab, 1 ixekizumab and 1 ustekinumab placebo-controlled RCTs and 1 adalimumab RCT using methotrexate as reference arm at weeks 11/12. For adults, out of 263 RCTs, 7 adalimumab and 15 etanercept (TNF inhibitors) and 4 ixekizumab and 12 ustekinumab (IL-17 and IL-12/23 inhibitors) RCTs reported PASI75/90 efficacy responses at weeks 11/12. Regarding efficacy, all biologics showed improved PASI responses over control arms. RRs ranges were 2.02-7.45 in PASI75 and 4.10-14.50 in PASI90. The highest PASI75 responses were seen for ustekinumab 0.375 mg/kg (RR=7.25, 95% CI 2.83-18.58) and ustekinumab 0.75 mg/kg (RR=7.45, 95% CI 2.91-19.06) in the CADMUS study. The highest PASI90 response was seen for ixekizumab (RR=14.50, 95% CI 4.82-43.58) in the IXORA-PEDS study. SAE incidences in pediatric and adult arms with biologics were 0 to 3% except for a pediatric arm with adalimumab 0.40 mg/kg (8%). For adults, pooled RR also showed improved PASI responses over placebo for all biologics, with highest PASI75 response observed for ixekizumab (pooled RR=16.18, 95% CI 11.83-22.14). Conclusions Both adults and children with psoriasis show superior efficacy with biologics compared to control arms after three months of treatment with SAE incidences in the low percentages. Additional longer-term clinical studies are warranted to fully understand the overall efficacy-safety profile of biologics in children with moderate-to-severe psoriasis.